Corrigendum to: ‘Dental implant placement with immersive technologies: A preliminary clinical report of augmented and mixed reality applications’ [The Journal of Prosthetic Dentistry (2024)] - Marcus, Engelschalk (2024)
The authors regret missing the acknowledgment to Marco Farronato for providing software support for the MR workflow, including access to the beta software program (Arreye s.r.l). The authors would like to apologize for any inconvenience caused.